The natural history of QTc interval and its clinical impact in coronavirus disease 2019 survivors after 1 year - Mojón-Álvarez, Diana; Izquierdo, Andrea; Cubero-Gallego, Héctor; Calvo-Fernández, Alicia; Marrugat, Jaume; Pérez-Fernández, Silvia; Cabero, Paula; Solà-Richarte, Claudia; Soler, Cristina; Farré, Núria; Vaquerizo, Beatriz (Frontiers in Cardiovascular Medicine, 2023)
Background and objective Prolonged QTc interval on admission and a higher risk of death in SARS-CoV-2 patients have been reported. The long-term clinical impact of prolonged QTc interval is unknown. This study examined the relationship in COVID-19 survivors of a prolonged QTc on admission with long-term adverse events, changes in QTc duration and its impact on 1-year prognosis, and factors associated with a prolonged QTc at follow-up. Methods We conducted a single-center prospective cohort study of 523 SARS-CoV-2-positive patients who were alive on discharge. An electrocardiogram was taken on these patients within the first 48 h after diagnosis and before the administration of any medication with a known effect on QT interval and repeated in 421 patients 7 months after discharge. Mortality, hospital readmission, and new arrhythmia rates 1 year after discharge were reviewed. Results Thirty-one (6.3%) survivors had a baseline prolonged QTc. They were older, had more cardiovascular risk factors, cardiac disease, and comorbidities, and higher levels of terminal pro-brain natriuretic peptide. There was no relationship between prolonged QTc on admission and the 1-year endpoint (9.8% vs. 5.5%, p = 0.212). In 84% of survivors with prolonged baseline QTc, it normalized at 7.9 ± 2.2 months. Of the survivors, 2.4% had prolonged QTc at follow-up, and this was independently associated with obesity, ischemic cardiomyopathy, chronic obstructive pulmonary disease, and cancer. Prolonged baseline QTc was not independently associated with the composite adverse event at 1 year. Conclusions Prolonged QTc in the acute phase normalized in most COVID-19 survivors and had no clinical long-term impact. Prolonged QTc at follow-up was related to the presence of obesity and previously acquired chronic diseases and was not related to 1-year prognosis.